A Study of Liver Function Tests in Patients Receiving Four Drugs Regimen in Initial Two Months as Antitubercular Drugs - Faiz, Saifun Nahar; Haque , Mahmudul; Hossain , Kamal; Alam , ASM Towhidul (Journal of Chittagong Medical College Teachers' Association, 2013)
Biochemical monitoring of liver function is essential because Anti Tubercular Therapy (ATT) induced hepatotoxicity can cause permanent injury to liver and death. This cross-sectional comparative study was conducted in department of Biochemistry of Chittagong Medical College during the period of July 2009- Jun 2010 to determine the association of Anti-TB treatment to alter the liver function in patients of intensive phase of tuberculosis taking Four Fixed Dose Combination of Isoniazid, Rifampicin, Pyrazinamide and Ethambutol. A total of 100 subjects were enrolled in this study. They were divided into two groups. Group A (case) was diagnosed case of tuberculosis and had taken anti TB drugs (four Fixed dose combination) at least for fifteen days and group B (control) was consisting of normal subjects. Serum ALT, AST, Bilirubin and prothrombin time were measured. It was found, that out of 70 subjects 20% had increased level of serum ALT, 17.1% had increased level of serum AST, 20% had increased level of serum bilirubin and only 2.9% had increased level of prothrombin time in case group. Finally, determination of liver functions in patients receiving Anti TB therapy (in intensive phase) should be done irrespective of presence or absence of established risk factors, to minimize not only the incidence but also the morbidity and mortality. JCMCTA 2012 ; 23 (2): 27-29